The Impact of Electric Vehicles on Automotive Aftermarket in 4-Wheeler Car Segment - Saurav Nandi; A Seetharaman; K Maddulety; Nada Sayarh Lebbar (STIE Malangkucecwara, 2026)
The extensive review and integration of management literature, this study draws on spares parts, battery durability, E-mobility technologies, infrastructure of recharging stations, govt policies and demand for battery electric vehicle, to develop a research framework that establishes the impact of electric vehicles on automotive aftermarket in 4-w segment. It further compares the effect of individual independent variables’ direct and indirect on the automotive aftermarket. The framework was tested in a survey applied to 330 to senior executives, middle managers, aftermarket stakeholders (dealers, distributors and technicians), policy makers etc. By considering the direct and indirect impacts the following ranks scored by govt polices, infrastructure of recharging stations, demand for battery electric vehicles, E-mobility technologies, spare parts and battery durability as first, second, third, fourth, fifth and sixth respectively. The suggestions provided in this paper ensures the benefits to practitioners as follows: significantly increase the profit potentials for automotive aftermarket stakeholders, demand for skilled technicians will elevate globally, consumer preference for battery electric vehicles in 4-w segment will surge, new business avenues for battery recharging stations will spread globally and demand for battery electric vehicles will rise exponentially.